A Post hoc analysis on rhythm and high intensity interval training in cardiac resynchronization therapy. (4th July 2019) - Melo, Xavier; Abreu, Ana; Santos, Vanessa; Cunha, Pedro; Oliveira, Mário; Pinto, Rita; Carmo, Miguel; Fernhall, Bo; Santa-Clara, Helena
Abstract: Objectives . Evaluate the effects of a 6-month High Intensity Interval Training (HIIT) program on (1) functional capacity and health-related quality of life, (2) multiple blood biomarkers, (3) echocardiographic parameters, and (4) exercise performance, in patients in cardiac resynchronization therapy (CRT) stratified by the presence of atrial fibrillation (AF), targeting the following questions: (1) Does CRT provide similar benefits in patients in AF and sinus rhythm (SR)?; and (2) Does HIIT provides similar benefits in patients in AF and SR? Design. Estimates were available at baseline and 6 months after CRT implantation in 37 patients with heart failure. Patients were randomized after CRT to a 24-week HIIT group or to a usual care group (CON). In this sub-analysis, HIIT (AF = 7; SR = 11) and CON (AF = 9; SR = 10) were stratified by the presence of AF. Results. Patients in AF benefitted to a lesser degree from CRT in functional status than patients in SR (23.8–46.0%). However, HIIT induced superior improvements in patients in AF compared to CON (23.9–61.0%). Decreases in TNF-α (8.5–42.9%), BNP (15.3–34.6%) and left ventricular mass (9.6–26.2%) were only observed in patients in SR, whereas increases in peak oxygen uptake were only observed in patients in AF (19.5–23.2%). HIIT improved exercise capacity (8.8–59.4%) in patients in SR. Conclusions. Patients in AF or SR undergoing CRT demonstrated distinct benefits from device implantation and from HIIT as an adjunctive therapeutic strategy. This suggests that both mainstay and adjunctive therapeutics may need to be managed differently in patients in AF and SR.